X-Ray Weak Active Galactic Nuclei from Super-Eddington Accretion onto Infant Black Holes - Piero Madau; Francesco Haardt (The Astrophysical Journal Letters)
A simple model for the X-ray weakness of James Webb Space Telescope–selected broad-line active galactic nuclei (AGNs) is proposed under the assumption that the majority of these sources are fed at super-Eddington accretion rates. In these conditions, the hot inner corona above the geometrically thin disk that is responsible for the emission of X-rays in “normal” AGNs will be embedded instead in a funnel-like reflection geometry. The coronal plasma will Compton upscatter optical/UV photons from the underlying thick disk as well as the surrounding funnel walls, and the high soft-photon energy density will cool down the plasma to temperatures in the range 30–40 keV. The resulting X-ray spectra are predicted to be extremely soft, with power-law photon indices Γ ≃ 2.8–4.0, making high- z super-Eddington AGNs largely undetectable by Chandra.